Evaluation of in vitro antibacterial effect of essential oil and some herbal plant extract used against mastitis pathogens. Issue 6 (17th October 2022) - Arbab, Safia; Ullah, Hanif; Bano, Iqra; Li, Ka; Ul Hassan, Inam; Wang, Weiwei; Qadeer, Abdul; Zhang, Jiyu
Abstract: Background: Mastitis in dairy cattle is a highly prevalent infectious disease, caused by various pathogens, mainly Staphylococcu aureus and Escherichia Coli, considerable economic loss worldwide. Objectives: The aim of this study was to evaluate the in vitro activity of Herbal plants used against S. aureus and E. coli bacteria which are the causative agents of mastitis. Methods: Therefore, in this study we investigate the antimicrobial effect of plant to evaluate the in vitro antibacterial activity of squaw mint ( Mentha pulegium L., Lamiaceae family), catnip ( Nepeta cataria L., Lamiaceae ), lemon balm ( Melissa officinalis L., Lamiaceae ), for mastitis treatment. Solutions prepared in fixed oils, against S. aureus and E. coli bacteria which are the main agents of mastitis. Isolation and antibiotic susceptibility analyses of milk samples taken from 100 subclinical mastitis dairy cows were performed. The antibacterial properties of the solutions were analysed by a disk diffusion method. Results: In the bacterial isolation, S. aureus was determined 97.7% and E. coli 53.5% positive of cows with mastitis. Antibacterial susceptibility test of the Lemon balm extract and essential oil showed maximum zone of inhibition against S. aureus 30 µl (23 mm), followed by 20 µl (19 mm), E . coli (19 mm) and 10 µl (5–7 mm), of the same extract against the Gram‐positive bacteria. The ethanol extracts show the similar activity against the Gram‐negative bacteria at 30, 20, and 10 µl (18–20 mm). Followed by S. aureus, when the zone areas for the susceptible solutions (Lemon balm, and essential oil) and the control group were compared, determined that there was little difference between for S. aureus and E. coli . Conclusions: This study hence indicated that in vitro cultured plantlets of lemon balm and peppermint oil can be used as the alternative method for production of mastitis and cheap source its precursor with antimicrobial activities. Abstract : Mastitis in dairy cattle is a highly prevalent infectious disease, caused by various pathogens, mainly Staphylococcu aureus, and Escherichia Coli, considerable economic loss worldwide. For the control of infection, some medicinal plant, Peppermint oil and lemon balm has an antimicrobial activity better than some antibiotics and can be used combined with other preservatives as a natural herbal drug in the treatment of mastitis.   Zone of inhibition (in mm) different conce ntration   Staphylococcus aureus Escherichia coli Plant extract 30 µl Act 20 µl Act 10 µl Act 30 µl Act 20 µl Act 10 µl Act Squaw mint 19 (+++) 12 (++) 5 (–) 18 (+++) (–) (+++) 3 (–) Lemon balm 23 (++++) 19 (+++) 7 (–) 19 (++++) 10 (++) (–) (–) Cantnip 8 (+) 5 (–) 2 (–) (–) (–) (–) (–) (–) (–) Essential oil 21 (++++) 15 (+++) 3 (–) 20 (++++) 14 (+++) 3 (–) Amoxicillin/ clavulanıc acid 15 (+++) 18 (+++) Cefoperazone 19 (+++) 20 (++++) Footnotes : (–): resistant; (+): less resistant; (++): medium sensitive, (+++): sensitive; (++++): very sensitive